Analisis Dampak Electronic Word Of Mouth (E-WOM) Dan Instagram Ads Terhadap Peningkatan Brand Awareness (Studi Kasus: Meat Service Denpasar) - Ni Nyoman Mona Laksmi Dewi; Ni Kadek Dessy Hariyanti; Luh Kemala Putri Widiari (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid growth of digital marketing has encouraged businesses to utilize social media as a strategic tool for building brand awareness. However, the implementation of Electronic Word of Mouth (e-WOM) and Instagram Ads among small and medium-sized enterprises (SMEs), particularly in the beef distribution industry, has not been fully optimized. Therefore, it is important to examine the effectiveness of these digital marketing strategies in enhancing consumer brand awareness. This study aims to analyze the influence of Electronic Word of Mouth (e-WOM) and Instagram Ads on Brand Awareness at Meat Service Denpasar, both partially and simultaneously. This study employed a quantitative approach using a survey research design. The study population consisted of audiences who had been exposed to Meat Service's Instagram content, while the sample comprised 120 respondents selected through purposive sampling. Primary data were collected using questionnaires, whereas secondary data were obtained from documentation and literature review. The data were analyzed using multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination analysis. The findings reveal that Electronic Word of Mouth (e-WOM) has a positive and significant effect on Brand Awareness by encouraging consumers to recognize and remember the Meat Service brand through online reviews, recommendations, and shared experiences. Instagram Ads also have a positive and significant effect on Brand Awareness and demonstrate a stronger influence than e-WOM by increasing audience exposure through visually appealing and informative promotional content. Furthermore, e-WOM and Instagram Ads simultaneously have a positive and significant effect on Brand Awareness. This study concludes that optimizing online consumer communication through Electronic Word of Mouth and maximizing the use of Instagram Ads are effective digital marketing strategies for improving Brand Awareness. These findings provide practical implications for Meat Service to strengthen its digital marketing activities, expand its market reach, reinforce its brand positioning, and enhance its competitiveness in the beef distribution industry.